• Asignatura: Matemáticas
  • Autor: Renatolokito15
  • hace 8 años

(-1/2) a la menos 2 ·(-1/2)a la menos 4 por favor

Respuestas

Respuesta dada por: Anónimo
2

Respuesta:

(4)(16)=64

Explicación paso a paso:

(-\frac{1}{2})^{-2}(-\frac{1}{2})^{-4} =  (-\frac{1}{2})^{-2-4}=(-\frac{1}{2})^{-6}=\frac{1}{\frac{1}{64} }=64

(-\frac{1}{2}) ^{-2}=\frac{1}{(-\frac{1}{2})^{2} }

\frac{1}{(-\frac{1}{2})^{2} } = \frac{1}{\frac{1}{4}}= 4

(-\frac{1}{2})^{-4} = \frac{1}{(-\frac{1}{2})^{4}}= 16

Preguntas similares